2002
DOI: 10.1159/000048431
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cations and Total Protein of Urine on the Solubility and Probability of Urate Stone Formation in Kidneys

Abstract: The solubility of uric acid kidney stones has been studied in water solutions containing ammonium ions, alkaline ions and alkaline earth metals. It was shown that the solubility of uric acid stones depends on the concentration of these cations. The shape of the dependence curve of uric acid stone solubility in solutions containing cations of ammonium, sodium, potassium, calcium and magnesium has an extreme character. It was shown that a maximal balanced solubility of stones occurs in solutions in which the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…When comparing the course of dependence S HUr =f([NH 4 + ]) in fig- 4 with the peculiarities of dissolution of uric acid stones in multicomponent salt systems, it is notable that availability of alkaline and alkaline-earth metal ions with simultaneous existence of ammonium ion leads to increase equilibrium solubility of uric acid stones. It is in complete conformity with previous results [1,5], in which it had been shown that, maximal S HUr in salt-solutions corresponds to "normal" concentration of cations in urine of healthy person. The role of amines in the systems, which were studied, is to increase supplementarily S HUr and to stabilize the process of dissolution of stones.…”
supporting
confidence: 93%
“…When comparing the course of dependence S HUr =f([NH 4 + ]) in fig- 4 with the peculiarities of dissolution of uric acid stones in multicomponent salt systems, it is notable that availability of alkaline and alkaline-earth metal ions with simultaneous existence of ammonium ion leads to increase equilibrium solubility of uric acid stones. It is in complete conformity with previous results [1,5], in which it had been shown that, maximal S HUr in salt-solutions corresponds to "normal" concentration of cations in urine of healthy person. The role of amines in the systems, which were studied, is to increase supplementarily S HUr and to stabilize the process of dissolution of stones.…”
supporting
confidence: 93%
“…In Figure 1 complete conformity with previous results [1,5], in which it had been shown that, maximal S HUr in salt-solutions corresponds to "normal" concentration of cations in urine of healthy person. The role of amines in the systems, which were studied, is to increase supplementarily S HUr and to stabilize the process of dissolution of stones.…”
supporting
confidence: 90%
“…Introduction. In our previous report we studied the influence of some anions and cations ([Cat n+ ]) (ammonium, sodium, potassium, calcium and magnesium) on the solubility (S) of uric acid (HUr) stones [1]. It was shown that, in water solutions, equilibrium solubility of uric acid stones in greater extent depends on the concentration of above mentioned cations.…”
mentioning
confidence: 99%
“…Among the proteins we observed to be up-regulated in the stone-formers, both ceruloplasmin and superoxide dismutase have been reported to be up-regulated in gene microarrays of rodent models of stone disease (21, 47). Both superoxide dismutase and ceruloplasmin have multiple cationic binding sites (48) and it has been suggested that urinary cationic concentration alters the solubility of stone crystals (49, 50). Ceruloplasmin has been best characterized for its role in copper transport and iron metabolism (9), however, we have not explored the role of these mechanisms in stone crystallization.…”
Section: Discussionmentioning
confidence: 99%